The Moderating Effect of Self-Efficacy on Pregnancy Stress and Smartphone Addiction of Pregnant Women in Late Pregnancy: A Longitudinal Study - Ma D; Li B; Liu X; Sun Y; Sun J (Dove Medical Press, 2024)
Di Ma, Bingfen Li, Xiaoyan Liu, Ying Sun, Jingli Sun Department of Gynaecology and Obstetrics, General Hospital of the Northern Theater Command, Shenyang, People's Republic of ChinaCorrespondence: Jingli Sun, Department of Gynaecology and Obstetrics, General Hospital of the Northern Theater Command, Shenyang, People's Republic of China, Email zg3416@sina.comPurpose: We aimed to understand the current situation of smartphone addiction in pregnant women, and explored the moderating effect of self-efficacy between pregnancy stress and smartphone addiction.Patients and Methods: This study adopted a longitudinal design to collect pregnant women from the obstetrics and gynecology department of a tertiary hospital in Shenyang in 2020 from early pregnancy (T1) to their late pregnancy (T2). A total of 342 questionnaires were collected, including the Smartphone Addiction Scale-Short Version (SAS-SV), the Pregnancy Pressure Scale (PPS), and the Chinese version of the General Self-Efficacy Scale (GSES). Multiple hierarchical regression and simple slope test were used to test the moderating effect of self-efficacy.Results: Smartphone addiction in T2 (44.74) was more sever than in T1 (33.11). The interaction item of T1 pregnancy stress and T2 self-efficacy was positively correlated with smartphone addiction (β=0.205, P< 0.01) and explained an additional 3.2% variance (ΔR2=0.032, P< 0.01). The influence of pregnancy stress on smartphone addiction was gradually decreased in the low, mean, and high groups of self-efficacy.Conclusion: Smartphone addiction in late pregnancy was more severe than that in early pregnancy, possibly due to increased pregnancy stress. The self-efficacy of pregnant women could reduce the impact of pregnancy stress on smartphone addiction. Medical staff can alleviate the bad behavior by improving their self-efficacy.Keywords: late pregnancy, pregnancy stress, smartphone addiction, self-efficacy, moderating effect